Negative-pressure wound therapy combined with artificial dermis (Terudermis) followed by split-thickness skin graft might be an effective treatment option for wounds exposing tendon and bone: A retrospective observation study. Issue 14 (9th April 2021) - Hsu, Kuo-Feng; Chiu, Yu-Lung; Chiao, Hao Yu; Chen, Chun-Yu; Chang, Chun-Kai; Wu, Chien-Ju; Peng, Yi-Jen; Wang, Chih-Hsin; Dai, Niann-Tzyy; Chen, Shyi-gen; Tzeng, Yuan-Sheng
Abstract : Abstract: Skin grafts are not suitable for closing tendon- or bone-exposing wounds, which require flap surgery. Dermal regeneration templates have value for closing such wounds, but the disadvantages of the technique include implantation failures because of infection, hematoma formation, or inappropriate immobilization. Negative-pressure wound therapy was reported to increase graft acceptance in difficult wounds. This retrospective case series of 65 patients evaluated negative-pressure therapy combined with artificial dermis for the treatment of acute or chronic tendon- or bone-exposing wounds. The artificial dermis was placed after adequate wound-bed preparation, with simultaneous application of a vacuum-assisted closure system. Split-thickness skin grafting was performed after the implanted artificial dermis had become established. The overall success rate was 88.1% (59/67): 88.6% (39/44) in the chronic wounds group and 87% (20/23) in the acute-trauma group separately. The overall mean survival time of artificial dermis in success cases was 13.24 ± 7.14 days. In separately, the survival time of artificial dermis had no statistically difference in chronic wound group (13.64 ± 7.53 vs 12.60 ± 5.86. P  = .943), but had significant statistical difference in acute trauma group (12.45 ± 6.44 days vs 23.33 ± 4.04 days, P  = .018). Also, comorbidity of PAOD was found a strong risk factor of failure in chronic wound group (100% vs 23.1%, P  < 0.001). We concluded that artificial dermis combined with negative-pressure therapy followed by split-thickness skin grafting might be a reliable and effective option for surgical reconstruction of tendon- or bone-exposing wounds, and could decreasing waiting periods of autologous skin graft.